Understanding cultural perceptions of sexuality in China and their influence on human papillomavirus vaccine hesitancy - Jiayuan Jin; Yanchao Han (Frontiers in Public Health)
IntroductionThe human papillomavirus (HPV) vaccine prevents infections that may result in precancerous lesions, cervical cancers, genital warts, and many other diseases. However, its uptake rate in China is 2.24%, and HPV vaccine hesitancy is widespread. This study aimed to identify whether cultural perceptions of sexuality in China influence HPV vaccine hesitancy and explore the correlation between sexual attitudes, sexual morality, and HPV hesitancy in Chinese.MethodsBetween January and April 2024, we adopted a qualitative approach and conducted in-depth, one-on-one, semi-structured interviews with 15 young female Chinese university students of sexual maturity.ResultsAlthough all college students exhibited vaccine hesitancy, their perceptions of vaccines and reasons for hesitation varied. This study classified hesitancy into three types: individuals hesitant owing to cultural conservatism and stigmatization, individuals with positive intentions but delayed vaccination, and overconfident individuals who disregarded vaccines. The reasons for vaccine hesitancy are linked to China’s conservative culture of sexuality, and Chinese sexual attitudes and morality have complex mechanisms that influence vaccination. Social taboos on sexual topics lead to inadequate sources of information regarding the HPV vaccine. Sexual morality is internalized into an individual’s subconscious, influencing the cognition of the vaccine. Negative associations and stigmatization of the vaccine further discourage vaccination.DiscussionVaccine hesitancy is not solely a medical or political-economic issue but also a deep-seated cultural issue. Culture significantly affects individual health behaviors, and ignoring socio-cultural factors can exacerbate public health problems. Future research should investigate the political-economic and socio-cultural factors to address geographic differences in vaccine hesitancy.